Sikap Keuangan, Lingkungan, dan Minat Bertransaksi Serta Pengaruhnya Terhadap Literasi Keuangan Syariah: Studi Empiris di Kota Banda Aceh - Muhammad Herizal Ihza; Muhammad Maulana; Muhammad Adnan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
Conventional financial literacy still dominates Islamic financial literacy, even though the Muslim population is the majority in Indonesia. The people of Banda Aceh City have increased after the implementation of Qanun No.11 of 2018 concerning the operation of Islamic financial institutions throughout Aceh. Public awareness of the importance of Islamic financial literacy is reflected in people's financial attitudes that are getting better, also supported by the environment (situation) that makes people increasingly adjust their Islamic financial literacy to environmental factors and the increasing interest of the community to transact in Islamic financial institutions makes people continue to strive to improve Islamic financial literacy. This study aims to analyze the influence of financial attitude, environment, and interest in transactions on Islamic financial literacy in the people of Banda Aceh City. The research uses a quantitative method with an associative approach. The results of the study show that partially the variables of financial attitude, environment, and interest in transactions have a positive and significant effect on Islamic financial literacy in the people of Banda Aceh City. This research can be used by the people of Banda Aceh City to continue to improve their Sharia financial literacy to the highest scale, which is very good because currently the community's Sharia financial literacy is still relatively good and this is a challenge for the Banda Aceh City Government to make regulations and policies that can help improve sharia financial literacy in the people of Banda Aceh City.